Ośrodki odpowiedzialności za koszty w przedsiębiorstwach gospodarki komunalnej - Piotrowska, Barbara (Responsibility Costs Centers for Municipal Company, 2005)
In the article it had been presented a conception to the isolation of responsibility costs centers for municipal company. The most important thing in this process are changes in the managements and application of responsibility accounting. Responsibility accounting gives opportunity to take a better position on increasing market competition.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 316-324